Influence of Seasonal Variations in Soil Water Availability on Gas Exchange of Tropical Canopy Trees. (14th July 2012) - Stahl, Clément; Burban, Benoit; Wagner, Fabien; Goret, Jean‐Yves; Bompy, Félix; Bonal, Damien
Abstract Seasonal variations in environmental conditions influence the functioning of the whole ecosystem of tropical rain forests, but as yet little is known about how such variations directly influence the leaf gas exchange and transpiration of individual canopy tree species. We examined the influence of seasonal variations in relative extractable water in the upper soil layers on predawn leaf water potential, saturated net photosynthesis, leaf dark respiration, stomatal conductance, and tree transpiration of 13 tropical rain forest canopy trees (eight species) over 2 yr in French Guiana. The canopies were accessed by climbing ropes attached to the trees and to a tower. Our results indicate that a small proportion of the studied trees were unaffected by soil water depletion during seasonal dry periods, probably thanks to efficient deep root systems. The trees showing decreased tree water status (i.e., predawn leaf water potential) displayed a wide range of leaf gas exchange responses. Some trees strongly regulated photosynthesis and transpiration when relative extractable water decreased drastically. In contrast, other trees showed little variation, thus indicating good adaptation to soil drought conditions. These results have important applications to modeling approaches: indeed, precise evaluation and grouping of these response patterns are required before any tree‐based functional models can efficiently describe the response of tropical rain forest ecosystems to future changes in environmental conditions.